Myopia and Inconsistency in Dynamic Utility Maximization - Strotz, R. H. (Review of Economic Studies, 1955)
Journal Article Myopia and Inconsistency in Dynamic Utility Maximization Get access R. H. Strotz R. H. Strotz Evanston, Illinois Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 23, Issue 3, 1955, Pages 165–180, https://doi.org/10.2307/2295722 Published: 01 December 1955